The adventurer's son : a memoir - Dial, Roman (William Morrow, an imprint of HarperCollinsPublishers, 2020)
In the predawn hours of July 10, 2014, the son of Alaskan scientist and National Geographic Explorer Roman Dial walked alone into Corcovado National Park, an untracked rainforest along Costa Rica's remote Pacific Coast. He carried a light backpack and machete. Cody emailed his father that he would do 4 days in the jungle and a day to walk out. He was never seen again. The authorities suspected murder. Dial was forced to confront the question: Was he responsible for his son's fate? -- adapted from jacket